Peripheral nervous system involvement in SARS-CoV-2 infection: a review of the current pediatric literature - Perilli, Lorenzo; Fetta, Marina; Capponi, Martina; Guido, Cristiana Alessia; Grosso, Salvatore; Iannetti, Paola; Spalice, Alberto (Frontiers in Neurology, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified as the pathogen responsible for the pandemic health emergency declared by the World Health Organization in March 2020. During the first part of the pandemic, adults showed mild to severe respiratory symptoms. Children seemed initially exempt, both from acute and subsequent complications. Hyposmia or anosmia were promptly identified as the main symptoms of acute infection, so neurotropism of SARS-CoV-2 was immediately suspected. (1, 2). As the emergency progressed, post infectious neurological complications were described also in pediatric population (3). Cases of cranial neuropathy in connection with acute SARS-CoV-2 infection have been reported in pediatric patients, as an isolate post infectious complication or in the context of the multisystem inflammatory syndrome in children (MIS-C) (4–6). Neuroinflammation is thought to be caused by several mechanisms, among which immune/autoimmune reactions (7), but so far, no specific autoantibody has been identified. SARS-CoV-2 can enter the central nervous system (CNS) directly and/or infect it retrogradely, through the peripheral nervous system (PNS), after replicating peripherally; several factors regulate invasion and subsequent neuroinflammation. Indeed, direct/secondary entry and replication can activate CNS-resident immune cells that, together with peripheral leukocytes, induce an immune response and promote neuroinflammation. In addition, as we will discuss in the following review, many cases of peripheral neuropathy (cranial and non-cranial) have been reported during or after SARS-CoV-2 infection. However, some authors have pointed out that the increase of cranial roots and ganglia in neurological imaging is not always observed in children with cranial neuropathy. (8). Even if a variety of case reports were published, opinions about an increased incidence of such neurologic diseases, linked to SARS-CoV-2 infection, are still controversial (9–11). Facial nerve palsy, ocular movements abnormalities and vestibular alterations are among the most reported issues in pediatric population (3–5). Moreover, an increased screen exposure imposed by social distancing led to acute oculomotion’s disturbance in children, not primarily caused by neuritis (12, 13). The aim of this review is to suggest food for thought on the role of SARS-CoV-2 in neurological conditions, affecting the peripheral nervous system to optimize the management and care of pediatric patients.